Silicon enhances yield and nitrogen use efficiency of tropical low land rice. (26th February 2020) - Mohanty, Sangita; Nayak, A. K.; Swain, C. K.; Dhal, B.; Kumar, Anjani; Tripathi, Rahul; Shahid, M.; Lal, B.; Gautam, P.; Dash, Goutam Kumar; Swain, P.
Abstract: High nitrogen (N) rate often leads to low yield of rice due to lodging and mutual shading. This study was conducted to ascertain whether silicon (Si) could enhance yield response of rice to higher N rate by enhancing rigidity of plant parts and improving photosynthesis. The effects of Si and N on crop growth, photosynthesis, N use efficiencies and yield of rice were investigated during wet season (June to November) in sub‐humid tropical region of India. An increasing trend in crop growth rate with Si at all levels of N was observed. Silicon reduced the flag leaf angle making the leaf more upright and enhanced flag leaf N content. Leaf chlorophyll concentration and single leaf photosynthesis rate were higher with Si compared to without Si at flowering stage. Both N and Si significantly affected panicle number and grain filling. Application of 200 kg SiO2 ha −1 and 100 kg N ha −1 produced the highest number of panicle per square meter, filled grain per panicle and yield. Significant yield increases ranging from 8.2–16.9% were observed with Si compared to without Si. Both N and Si treatments had significant effects on N uptake and N use efficiency. Agronomic N use efficiency and N recovery efficiency were higher with Si compared to without Si. The highest physiological N use efficiency was recorded with 200 kg SiO2 ha −1 and 80 kg N ha −1 . Silicon may enhance yield response of rice to higher N rate by improving source (photosynthetic) capacity and sink (reproductive organ) strength.